KOMUNIKASI PENDEK ETNOBOTANI DAMAR PADA ORANG RIMBA DI TAMAN NASIONAL BUKIT DUABELAS [Ethnobotany of Dammar by Orang Rimba in Bukit Duabelas National Park ] - Andhika, Rana Rio; Muhadiono, Muhadiono; Hilwan, Iwan (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Orang Rimba have local knowledge about utilization of dammar in Bukit Duabelas National Park .The research was aimed to record the type of dammar and explore local knowledge Orang Rimba utilizing dammar. Data were collected through interviews, participant observation and documentation . Data analysed as qualitative descriptive. There were 15 plant species whose resin were used by Orang Rimba i.e Dipterocarpus baudii, Dipterocarpus hasseltii, Hopea mengarawan, Hopea dryobalanoides, Dacryodes rugosa., Santiria laevigata, Shorea bracteolata, Parashorea aptera, Canarium pilosum, Shorea retinoides, Shorea cf. singkawang, Santiria dacryodifolia, Shorea multiflora dan Sarong (Trigona spp). Dammar were used Â as a fuel, medicine, adhesive material and traditional rituals. General use of dammar was for traditional Torch lighting (blebayon).